Temporal, biomechanical evaluation of a novel, transcatheter polymeric aortic valve in ovine aortic banding model - Kachel, Mateusz; Buszman, Piotr P.; Milewski, Krzysztof P.; Michalak, Magdalena; Domaradzki, Wojciech; Pruski, Maciej; Sobota, Michał; Fernandez, Carlos; Konopko, Marta; Nożyński, Jerzy; Kaźmierczak, Paweł; Włodarczyk, Jakub; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives To evaluate functionality, durability and temporal biocompatibility of a novel, balloon expanda-ble polymeric artificial transcatheter heart valve (ATHV) system (InFlow, CardValve Consorti-um, Poland). Along with expanding TAVI indications to low-risk group, the demand for new transcatheter valves is foreseen to increase drastically. Methods Surgical ascending aortic banding model was created in 20 sheep. Two weeks later, 16 were implanted with ATHV systems (15-16F). Three animals were sacrificed after 30, four - after 90 and six after 180-day follow-up. Follow-up transthoracic echocardiography (TTE) was per-formed. Results There was one procedure-related (6,25%) and two model-related deaths (12,5%). TTE revealed the flow gradients (max/average) of 30,75/17,91; 32,57/19,21 and 21,34/10,63 mmHg respec-tively. There were 2 cases of low-degree regurgitation after 180 days with no perivalvular leak observed. Histopathologic analysis showed no valve degeneration at terminal follow up. Conclusions The study showed good hemodynamic performance, durability, and biocompatibility of the novel ATHV.